Student Perceptions of the Use of Google Classroom and Zoom in Writing Skills Lectures during the Covid-19 Pandemic - Ihwan Rahman Bahtiar (Jurnal Educatio FKIP UNMA, 2021)
The Google Classroom and Zoom applications have become viral forms and are widely used in online learning in the era of the Covid-19 pandemic. These two applications are also used in online lectures in several foreign language education study programs at the Language and Arts Faculty, Jakarta State University. This study aimed to determine students' perceptions of the use of Google Classroom and Zoom in writing skills lectures. This research is a descriptive study involving 83 students from four foreign language education study programs. The data obtained were then analyzed using the Guttman scale. This study indicates that 69% of students consider using Google Classroom and Zoom effectively in writing skills lectures. Meanwhile, 68% stated that Google Classroom was and Zoom efficiently applied in writing skills courses. Then 67% feel their learning motivation has increased using Google Classroom and Zoom in writing skills lectures.